Economic preferences 2.0: Connecting competition, cooperation and inter-temporal preferences - Antonio M. Espín; Angel Martínez Sánchez; Benedikt Herrmann (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2017)
This paper presents a "second generation" theory on the nature of social preferences. Incorporating an inter-temporal ingredient, we generate an outcome-based model which focuses on the conflict between cooperation towards social efficiency and competition for the individual relative standing. We build on the argument that cooperative (competitive) patterns are more likely to arise when the future is perceived as secure and predictable (unsecure and unpredictable). In order to accommodate this argument with recent experimental results showing a relationship between individuals' inter-temporal preferences and social behavior in one-shot games, social efficiency is assumed to trigger long-run satisfaction whereas relative standing is linked to short-run satisfaction. In so doing, we add a dynamic component to social preferences. This feature of the model implies that more patient individuals are more willing to get involved in cooperative affairs while more impatient individuals are more likely to display competitive patterns. Yet, an individual's inter-temporal preferences interact with contextual factors (cues of future (un)predictability) to determine her course of action. The theory is then tested to shed new light on individuals' decisions in different games used in experimental research where a relationship between game play and inter-temporal preferences has been found. We show that our new combination of social and inter-temporal preferences adds well to the explanatory power of economic theory on human decision making.
Keywords: C91; D63; 330